2011
DOI: 10.1002/jcp.22302
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental role of microvilli in the main functions of differentiated cells: Outline of an universal regulating and signaling system at the cell periphery

Abstract: Until now, the general importance of microvilli present on the surface of almost all differentiated cells has been strongly underestimated and essential functions of these abundant surface organelles remained unrecognized. Commonly, the role of microvilli has been reduced to their putative function of cell-surface enlargement. In spite of a large body of detailed knowledge about the specific functions of microvilli in sensory receptor cells for sound, light, and odor perception, their functional importance for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
98
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 153 publications
2
98
0
Order By: Relevance
“…Microvilli are membrane protrusions that increase the surface area of cells and essential for perception and Ca 2+ signaling (Lange, 2011). Microvilli consist of a core of bundled actin filaments tethered laterally to the plasma membrane by a member of the ERM family (Fehon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Microvilli are membrane protrusions that increase the surface area of cells and essential for perception and Ca 2+ signaling (Lange, 2011). Microvilli consist of a core of bundled actin filaments tethered laterally to the plasma membrane by a member of the ERM family (Fehon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For enterocytes and kidney epithelial cells, the microvillus expands the surface over which absorption and secretion occur (1). NHE3 (SLC9A3) is an Na ϩ /H ϩ exchanger that is primarily localized to the microvilli, is responsible for the majority of small intestinal and renal Na ϩ absorption (2,3), and is highly regulated as part of physiologic function, which includes both stimulation and inhibition (4).…”
mentioning
confidence: 99%
“…Multiple classes of membrane proteins attach to these cytoskeletal structures, and it is assumed that they are relatively immobilized (1,18). FRAP studies with NHE3 have suggested that there are mobile as well as immobile pools of NHE3 in the microvilli and that under basal conditions NHERF1 and NHERF2 immobilize NHE3 and reduce its mobile fraction (19).…”
mentioning
confidence: 99%
“…Strikingly, expression of PC in MCF7 (and MDCK) potently induces formation of apical microvilli. Epithelial microvilli are common features in specialized epithelial layers involved in the secretion or absorption of nutrients, vesicles and proteins from the extracellular space (Lange, 2011). As we anticipated, full-length, exogenously expressed PC recruits NHERF-1, ezrin and Factin to apical membrane domains and forms microvilli in MCF7 cells.…”
Section: Podocalyxin's Function In Epithelial Architecture and Morphomentioning
confidence: 68%